WOMEN'S BODILY EXPERIENCES AS AN EPISTEMIC BASIS FOR KUPI’S QURANIC INTERPRETATION - Mahmudah, Nur; Islahuddin, Islahuddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Feminist scholarship has advanced reinterpretive approaches grounded in principles of justice and gender equality. These approaches seek to deconstruct entrenched patriarchal biases in Quranic Interpretation. They validate women’s knowledge and experiences as authoritative epistemic sources. The Congress of Indonesian Women Ulama (KUPI) places women's bodily experiences at the center of its gender-fair Quranic interpretation. This article aims to explore the epistemological basis of such interpretation. It does so by examining women’s bodily experiences, interpretive strategies, and implications. Using primary sources, including official KUPI documents and relevant literature, this study employs content analysis from a feminist standpoint theory by Harding. The study concludes that KUPI recognizes the unique experience of women's bodily experiences as an epistemological base of interpretation. KUPI has a strategy to integrate women's perspectives and experiences in reading the Quranic text. This process begins with problem identification and reflection, and proceeds to the construction of a re-narration of verse interpretation. KUPI's choice to utilize women's bodily experiences supports the documentation of women's experiences and the transformation of women's body knowledge into collective knowledge and communal narratives. This process legitimizes women’s bodily experiences as new, legitimate, and authoritative knowledge. KUPI's interpretative model affirms women’s bodily experience as an epistemic subject. This study contributes to Quranic scholarship on feminist tafsir or exegesis. It asserts women’s bodily experiences as an epistemic authority in Quranic exegesis, breaking masculine dominance and producing an Indonesian gender-fair interpretation.